Effects of dietary supplementation with whey proteins on surgical wound healing in rats - Sagliyan, A.; Ceribasi, A. O.; Gunay, C.; Han, M. G.; Benzer, F.; Kandemir, M. F. (Ecole Nationale Veterinaire Toulouse, 2010)
The purpose of this study was to macroscopically and histopathologically evaluate the healing of a surgically induced full thickness wound in rats fed with a diet enriched in whey proteins, and to locally analyze the oxidant/antioxidant status. A total of 50 female Wistar albino rats were randomly allotted in 2 equal groups (n = 25) according to the diet regimen: whereas control rats (group C) received a standard rat diet, animals from the second group (group W) were fed with the standard diet enriched with whey protein powder at the ratio 1:1. Fifteen days later, all rats were anaesthetized by intramuscular injection of xylazine HCI (5 mg/kg) and ketamine HCI (250 mg/kg) and after shaving and disinfection, a circular full thickness skin defect of 2 cm diameter was incised on the median line of the back area. Macroscopic and histological analyses as well as the measurements of the MDA (malondialdehyde) contents and GSH-Px (Glutathione peroxidase) activities in the surrounding area were performed 5, 9, 13, 17 and 21 days after the surgery. Macroscopically, the crust formation has more scarcely occurred and the wound cavity was more rapidly filled by a granulation tissue and collagen biosynthesis in rats of the group W than in controls, leading to a significant decrease of the wound area on days 5 and 9. The conventional histology has confirmed the early or/and more intense processes of re-epithelialisation, granulation tissue formation, collagen accumulation and angiogenesis as well as a more rapid decrease of the surgically induced inflammatory reaction in the group W. In parallel, the local oxidant/antioxidant status remained roughly unaltered whereas a marked reduction of the GSH-Px activity coupled to an intense MDA accumulation was observed on day 9 in controls and thereafter, the enzyme activity dramatically increased on day 17. These results clearly showed that the dietary supplementation with whey proteins can accelerate the wound healing, probably by controlling the local inflammation and the inherent free radical formation.
Keywords: Whey proteins; dietary supplementation; surgical wound; healing; rat; inflammation; malondialdehyde; glutathione peroxidase